The Oxford history of classical reception in English literature : Volume 1: 800-1558 - Copeland, Rita; Copeland, Rita (Oxford University Press, 2016)
A comprehensive investigation of the numerous and diverse ways in which literary texts of the classical world have stimulated responses and refashioning by English writers. This first volume covers the years 800-1558